The Comparison of Competitiveness of the USA and China - El Faraj, Alia (2016)
China is together with USA hand in hand top two leading economies, at the same time big partners and competitors. Aim of this thesis was to compare competitiveness of the USA and China and to find out which country is more competitive, on the basis of analyses of business environment, macroeconomic factors likewise through the Global Competitiveness report and Ease of Doing Business indicator. Thesis layout was divided into four chapters with subsections and sub-conclusions. Sub-conclusions were created for a fuller and more clear view, summary and analysis of each chapter. First chapter is general, consisting of definitions and a brief introduction to 21st Centurys superpowers. Followed by second chapter specialising in analyses of the business environment in China and the USA from economic, political and cultural factors. Third chapter is getting concentrated on macroeconomic overview. Last chapter is consisting of analyses and comparison of results from the previous chapters. This chapter is also composing of hypothesis of future development, future positioning of these superpowers and a SWOT-analyses.